Central skull base osteomyelitis secondary to invasive aspergillus sphenoid sinusitis presenting with isolated 12th nerve palsy. (2020) - Radhakrishnan, Suma; Mujeeb, Hiba; Radhakrishnan, Chandni
Abstract: Skull base osteomyelitis is a potentially life-threatening infection, usually seen in elderly immunocompromised patients secondary to malignant otitis externa (MOE) caused by Pseudomonas . Central or atypical skull base osteomyelitis often poses a diagnostic challenge as they present as head-ache with or without cranial nerve palsy often without any obvious source of infection. Although the incidence of fungal skull base osteomyelitis is increasing central skull base osteomyelitis due to invasive fungal sinusitis presenting with isolated hypoglossal nerve palsy has not been reported in the literature, to our knowledge. We report a case of a 59-year-old diabetic patient on regular treatment including steroid for acetylcholine receptor binding antibody positive myasthenia gravis with thymoma who presented with persistent head-ache and on evaluation, was found to have 12th cranial nerve palsy on the right side. She was diagnosed to have invasive fungal sphenoid sinusitis and central skull base osteomyelitis involving the clivus and was successfully treated with endoscopic transnasal transsphenoidal debridement followed by antifungal therapy.